Toward optimal-resolution NMR of intrinsically disordered proteins - Nováček, Jiří; Žídek, Lukáš; Sklenář, Vladimír (Journal of magnetic resonance (San Diego, Calif., 2014)
Proteins, which, in their native conditions, sample a multitude of distinct conformational states characterized by high spatiotemporal heterogeneity, most often termed as intrinsically disordered proteins (IDPs), have become a target of broad interest over the past 15years. With the growing evidence of their important roles in fundamental cellular processes, there is an urgent need to characterize the conformational behavior of IDPs at the highest possible level. The unique feature of NMR spectroscopy in the context of IDPs is its ability to supply details of their structural and temporal alterations at atomic-level resolution. Here, we briefly review recently proposed NMR-based strategies to characterize transient states populated by IDPs and summarize the latest achievements and future prospects in methodological development. Because low chemical shift dispersion represents the major obstacle encountered when studying IDPs by nuclear magnetic resonance, particular attention is paid to techniques allowing one to approach the physical limits of attainable resolution.
Keywords: IDPRs; algoritmy; nukleární magnetická rezonance biomolekulární; Algorithms; RDC; lidé; proteiny; RNAP δ-subunit; PRE; Protein Conformation; IDPs; zvířata; Humans; Multi-dimensional NMR; konformace proteinů; Non-uniform sampling; Proteins; Nuclear Magnetic Resonance, Biomolecular; NUS; Animals